REPORT ON THE ICDP WORKSHOP DOVE “DRILLING OVERDEEPENED ALPINE VALLEYS” (COMO AND VALTELLINA, 3-5 APRIL 2013) - Pini, Roberta (Alpine and Mediterranean Quaternary, 2021)
Here I provide a short report on the ICDP-funded Workshop DOVE (Drilling Overdeepened Alpine Valleys), held in Como and Valtellina between 3-5 April 2013. Discussion, led by the Project Principal Investigators, aimed at defining the scientifical issues and the financial budget of a multinational drilling initiative in and across the Alps.